Practicing (nature-based) tourism: Introduction - OLAFSDOTTIR, Gunnthora (Félag landfræðinga, 2011)
peer reviewed Little is still known about human practices in nature or elsewhere in the context of tourism. There are however positive signs of change in this respect in the wake of the cultural and performance ‘turn’ in academia. Phenomenological perspectives have emphasised investigation of the performative and hybrid aspects of living and moment-to-moment being and allows for deep scrutiny of human practices in the context of tourism. This paper discusses this change and its meaning for tourism studies as well as giving an overview of relevant literature that has made great contributions to this development. It then introduces this special issue of Landabréfið, which stems from the conference Practicing Nature-Based Tourism, which was held in Reykjavík, Iceland, on February 5-6, 2011. The papers in this issue provide different and insightful insights into how life is currently practiced in the context of (nature-based) tourism.